Academic writing apprehension in higher education: A systematic review - Joko Nurkamto; Lastika Ary Prihandoko; Nur Hidayanto Pancoro Setyo Putro; Oikurema Purwati (Universitas Syiah Kuala, 2024)
Considering the crucial skill required in formal education, specifically in higher education, academic writing is a part of every academic writers life. However, some writers often feel that they have insufficient knowledge of source use and academic writing. Responding to this issue, this systematic review aims to untangle factors encountered by the writers while having academic writing and the solution to cope with the problems. A literature search supported by Publish or Perish application explored academic articles published in Scopus and Web of Science databases from 2014 to 2022. Employing the PRISMA method, 19 academic articles in qualitative, quantitative, and mixed-method designs were selected to explore the issue. Exploring the selected articles, this systematic review resulted in the following findings: (1) the factors influencing students writing apprehension include unfamiliarity with academic tone and style, beliefs about writing, cognitive and behavioral anxiety, and insufficient support for writing; and (2) to cope with this writing apprehension, students may seek help from others, improve their writing strategies, and effectively manage writing feedback. Furthermore, faculty members should provide more appropriate teaching techniques and opportunities for students to share ideas with their peers to reduce writing anxiety and apprehension. The implications for pedagogical practices and future research directions are further discussed.